Business Intelligence in consolidation of financial statements - Karmańska, Anna (Business Intelligence w konsolidacji sprawozdań finansowych, 2019)
The aim of the paper is to analyze the use of Business Intelligence systems in the process of the financial consolidation and reporting in enterprises. This study describes the approaches adopted by companies while preparing consolidated financial statements. The paper is based on critical analysis of academic papers and vendor-specific consultants. The findings reveal that a spreadsheet can be sufficient for a simple consolidation usage. However, a dedicated consolidation software should be implemented when the structure of the group is complex. The consolidation software can add value to the organization by improving efficiency and maximizing information use
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 4 (54), s. 19-28
Keywords: informatyka ekonomiczna